Creative Accounting, Audit Risk and Audit Failure in Nigeria: What is the Auditor’s Perspective? - Augustine, Nwaorgu, Innocent; Chidoziem, Abiahu, Mary-Fidelis; Aondohemba, Iormbagah, Jacob; Amaechi, Egbunike, Patrick (International Journal of Economics, Business and Management Studies, 2019)
Creative accounting has taken a centre stage in the discussions around audit failures on the global stage. Several researches have sought to proffer solutions that aid organizations to avoid the potholes. This study however examined the Auditors’ perspective on the effect of creative accounting practices on audit risk and audit failure in Nigeria. The study employed survey research design using the Chi-square to analyze data gathered from questionnaires distributed to 115 practicing auditors from different geo-political zone in Nigeria. The findings of the study revealed that creative accounting has a significant effect on audit risk with a non significant effect on audit failure. Based on the results obtained from this study it is recommended that, Auditors should ensure that detailed attention is given to the detection of creative accounting practice by managers during the course of audit practice. Also, auditors must make sure that they adhere strictly to the dictates of the International Standards on Auditing in order to avoid failure of audit.